2009
DOI: 10.1590/s0100-06832009000600022
|View full text |Cite
|
Sign up to set email alerts
|

Boron mobility in eucalyptus clones

Abstract: SUMMARYUnderstanding the magnitude of B mobility in eucalyptus may help to select clones that are more efficient for B use and to design new practices of B fertilization. This study consisted of five experiments with three eucalyptus clones (129, 57 and 58) where the response to and mobility of B were evaluated. Results indicated that clone 129 was less sensitive to B deficiency than clones 68 and 57, apparently due to its ability to translocate B previously absorbed via root systems to younger tissues when B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
7
0
2
Order By: Relevance
“…Laboratory results for the twig + leaf component indicate that the B concentration was 62 (±1.5) 68 (±2.0) and 67 (±2.8) ppm when 0, 6 and 12 g of B, respectively, were applied. These concentrations are higher than those reported for the genus (Freitas et al, 2009) and three to five times higher than those found in other forest species fertilized with B such as T. grandis (Zhou et al, 2012) and Pinus radiata D. Don (Hawkins, Xue, Bown, & Clinton, 2010). It has been observed that fertilizing Betula pendula Roth seedlings with B can improve the concentration of this nutrient in the foliage by up to 50 % (Ruuhola, Leppanen, Julkunen-Tiitto, Rantala, & Letho, 2011).…”
Section: Contenido De Nutrimentos En Las Hojasmentioning
confidence: 66%
See 1 more Smart Citation
“…Laboratory results for the twig + leaf component indicate that the B concentration was 62 (±1.5) 68 (±2.0) and 67 (±2.8) ppm when 0, 6 and 12 g of B, respectively, were applied. These concentrations are higher than those reported for the genus (Freitas et al, 2009) and three to five times higher than those found in other forest species fertilized with B such as T. grandis (Zhou et al, 2012) and Pinus radiata D. Don (Hawkins, Xue, Bown, & Clinton, 2010). It has been observed that fertilizing Betula pendula Roth seedlings with B can improve the concentration of this nutrient in the foliage by up to 50 % (Ruuhola, Leppanen, Julkunen-Tiitto, Rantala, & Letho, 2011).…”
Section: Contenido De Nutrimentos En Las Hojasmentioning
confidence: 66%
“…The high B millas indican que la concentración de B fue de 62 (±1.5), 68 (±2.0) y 67 (±2.8) ppm cuando se aplicaron 0, 6 y 12 g de B, respectivamente. Estas concentraciones son mayores que las reportadas para el género (Freitas et al, 2009) y entre tres y cinco veces más altas que las encontradas en otras especies forestales fertilizadas con B como T. grandis (Zhou et al, 2012) y Pinus radiata D. Don (Hawkins, Xue, Bown, & Clinton, 2010). Se ha observado que la fertilización con B a brinzales de Betula pendula Roth puede favorecer la concentración de dicho nutrimento en el follaje hasta en 50 % (Ruuhola, Leppanen, Julkunen-Tiitto, Rantala, & Letho, 2011).…”
Section: Contenido De Nutrimentos En Las Hojasunclassified
“…José et al (2009) report that foliar B application in eucalyptus, using boric acid as a source, may be an alternative to rapid recovery of plants with symptoms of B deficiency. Those same authors state that foliar application of B can be a useful strategy, especially during the dry season because absorption of the element by the root occurs with less intensity due to drought.…”
Section: Resultsmentioning
confidence: 99%
“…The B applications via leaves, even after 20 and 26 months of the last application, resulted in greater foliar concentrations of B (Table 5), however, regardless of these applications; the concentrations were within the adequate range elaborated by Gonçalves (2011), 30-60 mg kg -1 of B. According to José et al (2009), the foliar application of B is a used strategy mainly in dry times, aiming at the lower absorption of the nutrient by the root. In this study, at 30 months after planting, we verified that the non-foliar application of B resulted in a foliar concentration close to the lower limit of the range considered adequate by Gonçalves (2011).…”
Section: ( )mentioning
confidence: 79%
“…In Cerrado soils that have low O.M. content, boron fertilization is common in the planting furrow, at the cultivation planting stage, and occasionally the B application via leaves has been employed in regions of prolonged dry period, in order to attenuate the effect of the lower B uptake by the roots during this period (José et al, 2009). However, there is still controversy regarding the B usage via leaves, due to its immobility in the phloem (Faquin, 2005), thus suggesting further studies that prove the efficiency of foliar fertilization in eucalyptus forests.…”
Section: Introductionmentioning
confidence: 99%